Solution of nonlinear equations using Mann iteration (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, we recall some basic concepts, properties of the spaces and some types of iteration approaches. Also, we give algorithm - fixed point iteration scheme and examples. Finally, we obtain the solution of nonlinear equations of the form using Mann iteration.